Monetary Union in West Africa : An Agency of Restraint for Fiscal Policies? - Pattillo, Catherine (IMF Working Papers; Working Paper ;, 2001)
Could a West African monetary union (either of the non-CFA countries, or all ECOWAS members) be an effective "agency of restraint" on fiscal policies? We discuss how monetary union could affect fiscal discipline and the arguments for explicit fiscal restraints considered in the European Monetary Union literature, and their applicability to West Africa. The empirical evidence, EMU literature, and CFA experience suggest that monetary union could create the temptation for fiscal profligacy through prospects of a bailout, or costs diluted through the membership. Thus, a West African monetary union could promote fiscal discipline only if the hands of the fiscal authorities are also tied by a strong set of fiscal restraints.